Pemilihan Alternatif Tanaman Obat Terhadap Penyakit Hipertensi Menggunakan Metode Analytical Network Process (ANP) dan Simple Multi Attribute Rating Technique (SMART) - Linda Pratiwi; Indriati Indriati; Ahmad Afif Supianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Medicinal plants contain active substances aims for healing and preventing of various types of diseases. Various types of medicinal plants each has certain criteria which result in difficulty in determining the alternative medicinal plants as the best priority. This research aims to select alternative medicinal plants which have nutritious substances for hypertension disease treatment. Not only nutritious substances, but also considering the price, availability and taste of the plant. Hypertension is a disease caused by high blood pressure. The selection of alternative medicinal plants for hypertension disease using Analytical Network Process (ANP) and Simple Multi Attribute Rating Technique (SMART) method. Analytical Network Process (ANP) method is used for determining the weights of each of the supporting criteria and Simple Multi Attribute Rating Technique (SMART) method is used for ranking of alternative medicinal plants selection. This research uses 10 data of medicinal plants to be tested. The result of Analytical Network Process (ANP) and Simple Multi Attribute Rating Technique (SMART) method use Spearman Rank correlation test with rs = 0.964 that means a relationship system and expert approach perfectly.